Rapid Recovery Control Method Based on Improved VDCOLs for Hybrid Multi-Infeed DC Transmission System After AC Failure - Mao, Chizu; Liu, Xianchao; Li, Qing; Xu, Zhihua; Xin, Yechun; Wang, Tuo (Frontiers in Energy Research, 2021)
Continuous commutation failure is very likely to occur in the hybrid Multi-infeed high-voltage direct current (HMIDC) after AC failure. In order to improve the recovery quality after HMIDC failure, an AC-DC voltage-dependent current order limiter (VDCOL) based on system strength index is proposed in this article. Firstly, the control mode transition process and system recovery process after DC failure are analyzed based on the hybrid multi-infeed DC transmission port model. Then, considering the impact of AC voltage and DC voltage input signals of VDCOL on AC voltage recovery and DC power recovery, respectively, the interaction factor and strength index of the hybrid multi-infeed system are constructed. Moreover, the weight coefficient of AC and DC voltage is calculated according to the strength of the multi-infeed system. Finally, a three-infeed hybrid DC transmission simulation model is built in the MATLAB/Simulink digital simulation platform. The simulation results demonstrate that the rapid recovery strategy proposed in this article can effectively suppress continuous commutation failure and improve the recovery speed of AC voltage and DC power.